The Grandest Madison Square Garden : Art, Scandal, and Architecture in Gilded Age New York - Hinman, Suzanne (Book collections on Project MUSE., 2019)
November 1891, the heart of Gilded Age Manhattan. Thousands filled the streets surrounding Madison Square, fingers pointing, mouths agape. After countless struggles, Stanford White-the country's most celebrated architect was about to dedicate America's tallest tower, the final cap set atop his Madison Square Garden, the country's grandest new palace of pleasure. Amid a flood of electric light and fireworks, the gilded figure topping the tower was suddenly revealed-an eighteen-foot nude sculpture of Diana, the Roman Virgin Goddess of the Hunt, created by Augustus Saint-Gaudens, the country's finest sculptor and White's dearest pal.0The Grandest Madison Square Garden tells the remarkable story behind the construction of the second, 1890, Madison Square Garden and the controversial sculpture that crowned it. Set amid the magnificent achievements of nineteenth-century American art and architecture, the book delves into the fascinating private lives of the era's most prominent architect and sculptor and the nature of their intimate relationship. Hinman shows how both men pushed the boundaries of America's parochial aesthetic, ushering in an era of art that embraced European styles with American vitality. Situating the Garden's seminal place in the history of New York City, as well as the entire country, The Grandest Madison Square Garden brings to life a tale of architecture, art, and spectacle amid the elegant yet scandal-ridden culture of Gotham's decadent era.